Gregarious Characteristics Based Social Aware Routing in Mobile Ad-Hoc Network - Vijayalakshmi, K; Manicka Chezian, R (International Journal of Computer Sciences and Engineering, 2025)
Mobile ad hoc Network (MANET) is a type of wireless mobile network that does not guarantee continuous network connectivity. Intermittently connected network (ICMAN) refers to the network where no end-to-end paths exist from time to time. However in normal MANET, usually end-to-end paths exist, which is not the case in ICMAN. This concept is also similar to Delay Tolerant Network, since both require a ‘store-carry-forward’ style of message propagation. In such a network, people move around and contact each other based on their common interests. The routing hence becomes a process to resolve the social feature differences between a source and a destination. Present social friendship avoid selfness node based Routing in which temporally differentiated friendships are used to make the forwarding decisions of messages. In a typical sensor network, where small packets generated by sensors need to be periodically reported to the base station, end-to-end delay plays a more important role. This paper presents how to achieve the minimum end-to-end delay for regular traffic through routing.